First reported case series of Candida krusei peritonitis secondary to a perforated viscus - Wong, Pearl; Gaszynski, Rafael; Gray, Andrew; Ghali, Mark; Farooque, Yasser; Merrett, Neil (International Surgery Journal, 2020)
Candida peritonitis is associated with high mortality and multiple organ failure. With an evolving epidemiology of candidaemia indicating an increasing prevalence of rare Candida species worldwide, consideration of multidrug-resistant fungal pathogens as a cause of abdominal sepsis is paramount. We report three cases of Candida krusei as a cause of secondary and tertiary peritonitis. These cases highlight that the early use of an echinocandin class antifungal in patients not responding to standard regimens warrants consideration.